Method for detecting energy efficiency of lithium iron phosphate material
By measuring the polarization factor and using the standard polarization factor-energy effect diagram to calculate the energy efficiency of lithium iron phosphate materials, the problem of long testing cycle, high cost and accuracy in existing technology, and realized more efficient, economical, and Reliable test method.
Patent Information
- Application Number
- CN202411410395.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-28
Smart Images

Figure CN119375574A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for detecting the energy efficiency of lithium iron phosphate materials. Background Art
[0002] At present, the development of energy conversion and storage technology is one of the key factors to promote scientific and technological progress and industrial upgrading. Among them, lithium battery technology has been widely used in portable electronic devices, electric vehicles and energy storage systems due to its advantages such as high energy density, long cycle life and environmental friendliness. With the continuous advancement of new energy technology, the requirements for lithium battery performance are also increasing, especially in the testing and evaluation of energy efficiency and stability.
[0003] In conventional technology, the energy efficiency test of lithium iron phosphate materials usually adopts the preparation of lithium iron phosphate material positive electrode sheets and graphite negative electrode sheets, and then assembles them into soft packs or cylindrical full batteries, and uses electrochemical testers to test the energy efficiency. This process includes multiple links such as homogenization, coating, rolling, slitting, lamination, baking, liquid injection, formation, capacity division and electrochemical testing. The process involved is complex and has strict requirements on the operating environment and material consistency.
[0004] However, conventional technologies have some significant defects in practical applications. First, the process of full-battery preparation and testing is time-consuming, usually requiring more than 20 days, which seriously affects the speed and efficiency of lithium iron phosphate material development. Secondly, the entire testing process consumes huge manpower and material resources, resulting in high testing costs. In addition, slight changes in test conditions, such as the consistency of negative electrode materials and fluctuations in ambient temperature, may cause large changes in energy efficiency test results, thereby affecting the accuracy and reliability of the test.
[0005] In conventional technology, there is a method to evaluate the polarization degree and energy efficiency of lithium iron phosphate by measuring the capacity of button-type half-cells at a specific voltage. Although this method provides an evaluation method, it is highly dependent on the consistency of button-type cells. In actual tests, even for batteries from the same batch, it is difficult to ensure that the voltage platform is completely consistent. A slight change in the voltage platform may cause a sharp fluctuation in the gram capacity at a specific voltage such as 3.2V, thereby affecting the accuracy of the test results.
[0006] In summary, the existing technology has many shortcomings in the energy efficiency testing of lithium iron phosphate materials, including long test cycle, high cost, sensitivity to test conditions, and the accuracy of results being affected by multiple factors. These problems not only limit the speed of material development, but also increase R&D costs and reduce R&D efficiency. Therefore, it is urgent to develop a new test scheme to shorten the test time, reduce costs, improve the accuracy and reliability of the test, and at the same time have higher compatibility with test conditions and battery consistency. Summary of the invention
[0007] The first purpose of the present invention is to provide a method for detecting the energy efficiency of lithium iron phosphate materials, wherein the method has the advantages of improving test accuracy, shortening test cycle, reducing costs, simplifying operation procedures, enhancing environmental adaptability, improving data repeatability, and promoting material optimization.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a method for detecting energy efficiency of a lithium iron phosphate material, comprising:
[0010] The polarization factors of the electrochemical performance of a standard battery including a standard lithium iron phosphate material with known energy efficiency and a battery to be tested including the lithium iron phosphate material to be tested are obtained by testing and calculating respectively, and the energy efficiency of the lithium iron phosphate material to be tested in the battery to be tested is calculated by comparing the energy efficiency and the polarization factor of the standard battery;
[0011] In an optional embodiment, the standard batteries of the standard lithium iron phosphate material with known energy efficiency are multiple groups, and the energy efficiency of the standard lithium iron phosphate material used in each group is different.
[0012] In an optional embodiment, the number of groups of standard batteries of standard lithium iron phosphate material with known energy efficiency is no less than 3.
[0013] In an optional embodiment, the standard battery and the battery to be tested are both button-type half-cells.
[0014] In an optional embodiment, the polarization factor of the electrochemical performance of a standard battery including a standard lithium iron phosphate material with known energy efficiency and a battery to be tested including the lithium iron phosphate material to be tested is obtained by testing and calculating respectively, and the energy efficiency of the lithium iron phosphate material to be tested in the battery to be tested is calculated by comparing the energy efficiency and the polarization factor of the standard battery, including:
[0015] Performing electrochemical tests and calculations on the standard battery and the battery to be tested respectively to obtain a first polarization factor corresponding to the standard battery and a second polarization factor corresponding to the battery to be tested;
[0016] Constructing a standard polarization factor-energy efficiency relationship diagram according to the first polarization factor of the standard battery and its corresponding energy efficiency;
[0017] Based on the standard polarization factor-energy efficiency relationship diagram, the energy efficiency corresponding to the battery to be tested is calculated using the second polarization factor.
[0018] In an optional embodiment, the electrochemical tests and calculations are performed on the standard battery and the battery to be tested respectively to obtain a first polarization factor corresponding to the standard battery and a second polarization factor corresponding to the battery to be tested, including:
[0019] The standard battery and the battery to be tested are used as target batteries and tested by the following methods respectively:
[0020] Performing charge and discharge cycles on the target battery, and recording the discharge voltage-specific capacity curve of the last cycle process;
[0021] Converting the discharge voltage-specific capacity curve into a voltage-lithiation depth curve within a preset lithiation depth range;
[0022] According to the voltage-lithiation depth curve, a target polarization factor corresponding to the target battery is obtained; the target polarization factor includes the first polarization factor of the standard battery and the second polarization factor of the battery to be tested.
[0023] In an optional embodiment, obtaining the target polarization factor corresponding to the target battery according to the voltage-lithiation depth curve includes:
[0024] Calculate the target curve integral area of the target battery according to the voltage-lithiation depth curve;
[0025] Based on the preset lithiation depth range and the preset voltage range, intercepting a rectangular area including the voltage-lithiation depth curve, and calculating a target rectangular area of the rectangular area;
[0026] A target polarization factor of the target battery is calculated according to the target curve integral area and the target rectangular area of the target battery.
[0027] In an optional embodiment, the preset lithiation depth ranges from 40% to 100%;
[0028] In an optional implementation, the preset voltage range is 2.00V to 3.75V.
[0029] In an optional embodiment, the rectangular area where the voltage-lithiation depth curve is located is a rectangular area with 40% to 100% lithiation depth as the horizontal side, the 40% lithiation depth as the base point and the vertical side with a height of 2.00V to 3.75V.
[0030] In an optional embodiment, the target polarization factor is calculated as follows:
[0031]
[0032] Wherein, α represents the target polarization factor; S0 represents the target curve integral area; S1 represents the target rectangular area.
[0033] In an optional embodiment, the target battery is subjected to a charge-discharge cycle, wherein the number of cycles is not less than 2 times;
[0034] In an optional embodiment, the current density of the charge and discharge cycle ranges from 50 mA / g to 100 mA / g.
[0035] In an optional embodiment, before respectively testing and calculating the polarization factors of the electrochemical performance of the standard battery including the standard lithium iron phosphate material with known energy efficiency and the battery to be tested including the lithium iron phosphate material to be tested, the method further includes:
[0036] A standard sample and a sample to be tested are prepared respectively; wherein the standard sample is a positive electrode sheet prepared from a lithium iron phosphate material with known energy efficiency; and the sample to be tested is a positive electrode sheet prepared from a lithium iron phosphate material to be tested;
[0037] The standard sample and the sample to be tested are assembled separately to obtain a standard battery including the standard sample and a battery to be tested including the sample to be tested.
[0038] In an optional embodiment, the preparing the standard sample and the sample to be tested separately comprises:
[0039] Dispersing the conductive material, the lithium iron phosphate material, and the binder into a dispersant to obtain a homogeneous slurry;
[0040] The homogenized slurry is coated on the surface of the carbon-coated aluminum foil, and the standard sample and the sample to be tested are obtained after drying;
[0041] Preferably, the conductive material comprises at least one of carbon nanotubes, graphene and conductive carbon black;
[0042] Preferably, the binder comprises polyvinylidene fluoride;
[0043] Preferably, the dispersant used comprises N-methylpyrrolidone;
[0044] Preferably, the surface density of the standard sample and the sample to be tested is 100 g / m 2 ~180g / m 2 .
[0045] Compared with the prior art, the beneficial effects of this application are:
[0046] (1) This application directly measures the polarization factor, and the method can more accurately evaluate the energy efficiency of lithium iron phosphate materials. The polarization factor is a key parameter in electrochemical performance, which reflects the energy loss of the battery during the charging and discharging process. By accurately measuring this parameter, the actual performance of the material can be more truly reflected.
[0047] (2) Compared with the traditional full-battery preparation and testing method, this method may reduce multiple preparation links, thereby significantly shortening the testing cycle. This not only speeds up the material development and evaluation, but also improves R&D efficiency.
[0048] (3) Since the materials and labor required to prepare the full battery are reduced, this method can reduce the overall testing cost. This is particularly important for large-scale material screening and evaluation because it allows more samples to be tested at a lower cost.
[0049] (4) This method may simplify the test process, making the operation more convenient and faster. The simplified operation process not only reduces the possibility of human error, but also makes the test process easier to standardize and automate.
[0050] (5) Since this method relies on direct measurement of electrochemical properties, it may have lower requirements for the test environment, thereby reducing the impact of environmental factors on the test results and improving the stability and reliability of the test.
[0051] (6) This method may not be limited to specific battery structures or materials, but can be applied to the energy efficiency evaluation of a variety of lithium iron phosphate materials, with good compatibility and universality.
[0052] (7) Through standardized testing procedures and precise polarization factor measurement, this method can provide reproducible test results, which is crucial for material performance evaluation in scientific research and industrial applications.
[0053] (8) Accurate energy efficiency evaluation helps to quickly identify the advantages and disadvantages of materials, thereby guiding the optimization and improvement of materials and promoting further improvement of the performance of lithium iron phosphate materials.
[0054] In summary, this method for testing the energy efficiency of lithium iron phosphate materials provides an efficient, economical and reliable solution for the research and development and application of lithium iron phosphate materials by improving test accuracy, shortening test cycles, reducing costs, simplifying operating procedures, enhancing environmental adaptability, improving data repeatability and promoting material optimization. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0056] Figure 1 This is a standard polarization factor-energy efficiency relationship diagram in the embodiments of this application;
[0057] Figure 2 It is a rectangular area containing the voltage-lithiation depth curve in the embodiment of the present application;
[0058] Figure 3 This is a relationship diagram between the energy efficiency and the polarization factor calculated in the embodiments of the present application. DETAILED DESCRIPTION
[0059] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0060] In an embodiment of the present application, a method for detecting energy efficiency of a lithium iron phosphate material is provided, comprising:
[0061] Step S100, respectively testing and calculating the polarization factors of the electrochemical performance of a standard battery including a standard lithium iron phosphate material with known energy efficiency and a battery to be tested including the lithium iron phosphate material to be tested, and calculating the energy efficiency of the lithium iron phosphate material to be tested in the battery to be tested by comparing the energy efficiency and the polarization factor of the standard battery.
[0062] As mentioned above, polarization factor is a concept in electrochemistry, which describes the energy loss caused by the incomplete reversibility of electrochemical reactions during the charge and discharge process of the battery. This energy loss is usually manifested as the change in voltage of the battery during the charge and discharge process, that is, the difference between the voltage of the battery during actual operation and the voltage under ideal conditions.
[0063] The size of the polarization factor directly affects the energy efficiency and power output of the battery. In battery design and material development, reducing polarization is the key to improving battery performance. By measuring and analyzing the polarization factor, we can better understand and optimize the battery's charge and discharge behavior and improve the overall performance of the battery.
[0064] As mentioned above, the energy efficiency of lithium batteries refers to the ratio of the effective energy that the battery can output to the input energy during the battery charging and discharging process. This ratio reflects the efficiency of the battery in the energy conversion process and is one of the important parameters for measuring battery performance.
[0065] Specifically, the energy efficiency of lithium batteries can be defined by the ratio of energy output during discharge to energy input during charging. Systematically calculating the energy efficiency value over the entire service life of the battery can reveal the main linear trend of battery efficiency. There are many factors that affect the energy conversion efficiency of lithium-ion batteries, including raw materials, design, process, etc. Different detection methods will also lead to different energy conversion efficiency values measured for the same product.
[0066] In the embodiment of the present application, a standard battery of a standard lithium iron phosphate material with known energy efficiency is used as a reference in order to provide a reliable benchmark to compare and quantify the energy efficiency of the battery to be tested. This comparison method can improve the accuracy and repeatability of the test because it allows the energy efficiency of the battery to be tested to be evaluated by directly comparing the polarization factor of the battery to be tested with that of the standard battery. The standard battery serves as a benchmark to ensure the consistency of the test results and reduce errors caused by slight changes in test conditions, such as temperature fluctuations or slight inconsistencies between batteries.
[0067] In addition, using a standard cell as a reference allows for a more direct assessment of the performance of the battery under test, as it provides a clear energy efficiency target. This approach is common in electrochemical performance testing, and it helps to quickly identify the strengths and weaknesses of materials and guide further material optimization and battery design improvements.
[0068] With this approach, researchers and engineers can more effectively evaluate the potential of new lithium iron phosphate materials and compare them with existing standard materials. This will not only help accelerate the development of new materials, but also help ensure that the quality and performance of the final product meet the energy efficiency requirements of specific applications.
[0069] Furthermore, the standard batteries of the standard lithium iron phosphate material with known energy efficiency are in multiple groups, and the energy efficiency of the standard lithium iron phosphate material used in each group is different.
[0070] Furthermore, the number of groups of standard batteries of standard lithium iron phosphate material with known energy efficiency is not less than 3.
[0071] As mentioned above, there can be multiple standard batteries of standard lithium iron phosphate materials with known energy efficiency in theory, which is similar to using multiple standard samples in scientific experiments to improve the accuracy and reliability of test results. Using multiple standard batteries can reduce the accidental errors that may exist in a single sample, and more accurate energy efficiency data can be obtained by taking the average or performing statistical analysis.
[0072] In order to improve accuracy, the following points should be noted when setting the standard battery:
[0073] Consistency: Ensure that all standard batteries are highly consistent in material, structure and manufacturing process to reduce batch-to-batch differences.
[0074] Stability: The standard battery should have good electrochemical stability to ensure that the performance does not change significantly during the test cycle.
[0075] Accurate energy efficiency value: The energy efficiency value of the standard battery should be determined through rigorous testing and calibration to ensure its accuracy.
[0076] Environmental control: Environmental conditions such as temperature and humidity should be strictly controlled during the test, as these factors may affect battery performance.
[0077] Standardization of test methods: Use standardized test methods and equipment to ensure repeatability and comparability of results for each test.
[0078] In addition, statistical methods can be used to analyze the test results of multiple standard batteries, such as calculating the average value, standard deviation, etc., to evaluate the central tendency and dispersion of the data. Through these measures, the accuracy of the standard battery as a reference can be improved, making the energy efficiency evaluation of the battery to be tested more accurate and reliable.
[0079] A standard curve can be constructed by selecting multiple standard batteries made of lithium iron phosphate materials with different energy efficiencies. This method can improve the accuracy and reliability of the test results because it allows the energy efficiency of the battery to be evaluated by comparing the polarization factor of the battery to be tested with the polarization factors of a series of standard batteries with known energy efficiencies.
[0080] Specifically, by selecting standard batteries with different energy efficiencies, a wider range of energy efficiencies can be covered, thereby providing a more comprehensive and accurate energy efficiency evaluation for the battery to be tested. These standard batteries should be representative and able to reflect the performance changes of lithium iron phosphate materials in actual applications. By comparing the polarization factor of the battery to be tested with the polarization factor of the standard battery, a relationship diagram between the polarization factor and the energy efficiency, i.e., the standard curve, can be constructed, thereby achieving accurate calculation of the energy efficiency of the battery to be tested.
[0081] In actual operation, the polarization factors of the standard battery and the battery to be tested can be obtained through electrochemical testing methods such as cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Then, statistical methods or mathematical models such as regression analysis are used to determine the relationship between the polarization factor and energy efficiency, and to construct a standard curve. This method not only improves the accuracy of the test, but also helps to quickly identify the advantages and disadvantages of the material, guiding further material optimization and battery design improvements.
[0082] Furthermore, the standard battery and the battery to be tested are both button-type half-cells.
[0083] The method provided in the embodiments of the present application can be limited to a button-type half-battery.
[0084] Button half-cells were chosen as the standard and test battery for the energy efficiency test of lithium iron phosphate materials mainly because they are small in size, easy to operate, and convenient for accurate electrochemical performance testing. This type of battery makes the experimental conditions easy to control, ensuring the consistency and repeatability of the test. At the same time, the standardized design of button half-cells helps to directly reflect the performance of the material itself and reduce the interference of other variables. They are more economical in cost, suitable for large-scale material screening, and have advantages in safety with lower risks. In addition, button half-cells are simple to assemble and disassemble, which is convenient for various tests, further shortening the test cycle. The data is highly comparable and easy to compare horizontally, providing an effective experimental platform for accelerating the research and development and optimization of battery materials.
[0085] In addition, without considering factors such as test cycle, efficiency, cost, operation, assembly convenience, volume, etc., other types of batteries can also be used for testing using the method in the embodiments of the present application, which will not be repeated here.
[0086] Compared with the technical solution commonly used in traditional technology to prepare lithium iron phosphate-graphite full batteries to obtain energy efficiency, the method in the embodiment of the present application takes less time and the energy efficiency information of the material can be obtained in three days, while the traditional technical solution takes more than 20 days.
[0087] Compared with the complicated and lengthy process of preparing stacked / cylindrical batteries, the method in the embodiment of the present application only needs to prepare button-type half-cells, which is lower in cost and can save a lot of manpower and material resources, and the cost reduction can reach more than 90%.
[0088] Further, the step S100, respectively testing and calculating the polarization factor of the electrochemical performance of a standard battery including a standard lithium iron phosphate material with known energy efficiency and a battery to be tested including the lithium iron phosphate material to be tested, and calculating the energy efficiency of the lithium iron phosphate material to be tested in the battery to be tested by comparing the energy efficiency and the polarization factor of the standard battery, includes:
[0089] Step S1, performing electrochemical tests and calculations on the standard battery and the battery to be tested respectively, to obtain a first polarization factor corresponding to the standard battery and a second polarization factor corresponding to the battery to be tested.
[0090] As mentioned above, electrochemical tests are performed on the standard battery and the battery to be tested respectively, and the electrochemical performance parameters of the battery during the charge and discharge process can be obtained through these tests. The same test process is involved for the two batteries (standard battery and test battery) to ensure the comparability of the results. Thus, the polarization factors of the two batteries are obtained, the first polarization factor corresponds to the standard battery, and the second polarization factor corresponds to the test battery.
[0091] The polarization factor obtained through direct testing can accurately reflect the electrochemical performance of the battery and provide a data basis for subsequent energy efficiency evaluation.
[0092] Specifically, for example, electrochemical testing techniques such as cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) may be used.
[0093] Step S2, constructing a standard polarization factor-energy efficiency relationship diagram according to the first polarization factor of the standard battery and its corresponding energy efficiency.
[0094] Using the relationship between the polarization factor and energy efficiency of a standard battery with known energy efficiency, a relationship diagram for reference is constructed, such as Figure 1 As shown. Through data analysis methods, such as regression analysis, the mathematical relationship between the polarization factor and the energy efficiency is found, thereby forming a chart or mathematical model, which can predict the energy efficiency of the battery through the polarization factor.
[0095] In this step, a standardized reference is provided to facilitate rapid evaluation and comparison of the energy efficiency of different batteries. Specifically, data processing software can be used for graphing and model fitting.
[0096] Step S3, based on the standard polarization factor-energy efficiency relationship diagram, using the second polarization factor, calculate the energy efficiency corresponding to the battery to be tested.
[0097] Using the model constructed in the second step, the energy efficiency of the battery to be tested is calculated according to the second polarization factor. The polarization factor of the battery to be tested is input into the model, and the corresponding energy efficiency is calculated to obtain the energy efficiency value of the battery to be tested, which can be used for performance evaluation and material optimization.
[0098] The method is simple and fast, can directly reflect the energy efficiency performance of materials, and help accelerate the development and screening of battery materials. The calculation can be achieved by writing algorithms or using ready-made data analysis tools.
[0099] Furthermore, the step S1, performing electrochemical tests and calculations on the standard battery and the battery to be tested respectively, to obtain a first polarization factor corresponding to the standard battery and a second polarization factor corresponding to the battery to be tested, includes:
[0100] Step S11, taking the standard battery and the battery to be tested as target batteries, and testing them respectively by the following methods:
[0101] The reasons for using the same method to test the standard battery and the battery to be tested are as follows:
[0102] (1) Ensure comparability of test results: Using the same test method can ensure consistency in test conditions, including the use of test equipment, control of the test environment, and execution of test steps, thereby ensuring that the data obtained can be directly compared.
[0103] (2) Reduce variables: In scientific experiments and engineering practice, controlling variables is the key to accurately evaluating material properties. By using a unified test method, errors caused by inconsistent test conditions can be reduced, making the test results more reliable.
[0104] (3) Improve the repeatability and reproducibility of tests: Standardized test methods help improve the repeatability of experiments and ensure consistent test results at different times, between different operators or different laboratories.
[0105] (4) Ease of data analysis and interpretation: When the test methods are consistent, the collected data is easier to statistically analyze and interpret. This is crucial for subsequent performance optimization and material improvement.
[0106] By adopting the same testing method, the performance of different batteries can be evaluated and compared more accurately, providing strong data support for the research and development and optimization of battery materials.
[0107] Step S111, performing charge and discharge cycles on the target battery, and recording a discharge voltage-specific capacity curve of the last cycle process;
[0108] This step involves actual charge and discharge cycles of the standard battery and the battery to be tested to simulate the performance of the battery under normal use conditions. The battery is charged and discharged to a preset voltage range multiple times, usually including charging to the rated voltage and discharging to the cut-off voltage, so as to obtain the discharge voltage-specific capacity curve of the battery in the last charge and discharge cycle, which reflects the change of voltage with specific capacity during the battery discharge process.
[0109] Through charge and discharge cycles, the battery's cycle stability and energy efficiency performance can be evaluated, providing necessary data for subsequent polarization factor calculations.
[0110] Specifically, a battery testing system may be used to perform automated charge and discharge cycle testing and record corresponding voltage and specific capacity data.
[0111] In the method for testing the energy efficiency of lithium iron phosphate materials, the selection of standard batteries with multiple standard lithium iron phosphate materials with different known energy efficiencies is to establish a reliable benchmark for evaluating the energy efficiency of the battery to be tested. This method is similar to constructing a standard curve, in which the energy efficiency of each standard battery is used as a reference point to help determine the energy efficiency of the battery to be tested.
[0112] It should be noted that during the battery's charge and discharge cycle, the battery's performance may change, especially in the early stages of the cycle, where it may undergo some "activation" or "stabilization" processes. Taking the discharge voltage-specific capacity curve of the last cycle after multiple cycles can ensure that the battery's performance data is obtained in a stable state after a certain number of cycles, which helps reduce the impact caused by the initial unstable state of the battery, thereby obtaining more accurate and representative results.
[0113] The above discharge voltage-specific capacity curve shows the change of voltage with specific capacity (or capacity percentage) during battery discharge. Specific capacity refers to the amount of electricity released per unit mass of active material in the battery during discharge.
[0114] On this curve, the horizontal axis represents the specific capacity of the battery discharge, and the vertical axis represents the battery voltage. The shape of the curve can reflect the discharge characteristics of the battery, such as discharge platform, voltage drop, etc.
[0115] The discharge voltage-specific capacity curve can be obtained in the charge and discharge cycle test of the battery, especially under constant current discharge conditions, recording the change of battery voltage over time or discharge amount.
[0116] Step S112, converting the discharge voltage-specific capacity curve into a voltage-lithiation depth curve within a preset lithiation depth range;
[0117] The discharge voltage-specific capacity curve is converted into a voltage-lithiation depth curve to analyze the electrochemical performance of the battery at different lithiation states. According to the specific capacity data of the battery, it is converted into the lithiation depth of the battery (that is, the degree to which lithium ions are embedded in the positive and negative electrode materials) to obtain a voltage-lithiation depth curve, which can more intuitively reflect the voltage response of the battery at different lithiation states.
[0118] Curve conversion helps to more accurately evaluate the electrochemical polarization of the battery during the charge and discharge process and provides a basis for calculating the polarization factor.
[0119] Specifically, data processing software can be used to convert the curve according to the relationship between the specific capacity of the battery and the lithiation depth.
[0120] Step S113, obtaining a target polarization factor corresponding to the target battery according to the voltage-lithiation depth curve; the target polarization factor includes the first polarization factor of the standard battery and the second polarization factor of the battery to be tested.
[0121] The polarization factor of the battery is calculated based on the voltage-lithiation depth curve to evaluate the energy loss of the battery during the charge and discharge process. The voltage-lithiation depth curve is analyzed to determine the polarization degree of the battery during the charge and discharge process, and the polarization factor is calculated based on this to obtain the first polarization factor of the standard battery and the second polarization factor of the battery to be tested. These factors are key parameters for evaluating battery energy efficiency.
[0122] The calculation of polarization factor helps to identify the bottleneck of battery performance and provide a basis for the optimization of battery materials and the improvement of battery design. The polarization factor is calculated by the specific algorithm of voltage-lithiation depth curve through electrochemical test data analysis software.
[0123] The voltage-lithiation depth curve is a curve that converts the discharge voltage-specific capacity curve into a voltage-lithiation depth (or lithium ion concentration) curve. The lithiation depth refers to the degree of lithium ion embedding in the electrode material, and is usually used to describe the change in lithium ion concentration in the positive and negative electrode materials during the battery charging and discharging process.
[0124] The horizontal axis of this curve is the depth of lithiation, usually expressed as a percentage or a specific concentration unit, and the vertical axis is the battery voltage. Through this conversion, the electrochemical performance of the battery at different lithiation states can be analyzed more intuitively.
[0125] Furthermore, the step S113, obtaining a target polarization factor corresponding to the target battery according to the voltage-lithiation depth curve, includes:
[0126] Step S1131, calculating the target curve integral area of the target battery according to the voltage-lithiation depth curve;
[0127] As mentioned above, the integral area of the voltage-lithiation depth curve of the target battery is calculated. This integral area can reflect the total change in energy of the battery during the discharge process and is an important parameter for measuring battery performance. By integrating the area under the curve of the battery voltage changing with the lithiation depth, the total energy released by the battery during the entire discharge process can be obtained.
[0128] The integral area of a curve refers to the area of the region enclosed by the curve and the horizontal axis within a certain range. Mathematically, this is usually calculated by integration. For a battery discharge voltage-specific capacity curve or voltage-lithiation depth curve, the integral area of the curve can represent the total energy released by the battery during the discharge process.
[0129] Specifically, during the discharge process of the battery, the change in voltage over time or specific capacity can be plotted as a curve. The area under this curve, calculated by integration, represents the total energy provided by the battery during the entire discharge cycle.
[0130] This integrated area is an important parameter in battery testing and analysis because it provides a quantitative measure of the energy output of the battery under specific discharge conditions. By comparing the integrated areas of different batteries or under different conditions, the battery's performance, such as energy density and discharge efficiency, can be evaluated.
[0131] Step S1132, based on the preset lithiation depth range and the preset voltage range, intercepting a rectangular area including the voltage-lithiation depth curve, and calculating a target rectangular area of the rectangular area;
[0132] Above, reference Figure 2 Based on the preset lithiation depth range and voltage range, a rectangular area containing the voltage-lithiation depth curve is intercepted and the area of the rectangle is calculated. This rectangular area represents the theoretical energy output of the battery within a specific lithiation depth and voltage range, which can be used to compare with the actual discharge situation and evaluate the battery performance.
[0133] Step S1133, calculating a target polarization factor of the target battery according to the target curve integral area and the target rectangular area of the target battery.
[0134] The polarization factor of the target battery is calculated based on the integral area of the voltage-lithiation depth curve of the target battery and the area of the above intercepted rectangle. The polarization factor is a parameter that describes the energy loss of the battery during the charge and discharge process. Calculating the polarization factor can help understand the electrochemical performance of the battery and possible polarization phenomena.
[0135] The advantage of these steps is that they provide a method for quantitatively analyzing battery performance. By calculating the polarization factor, the energy efficiency and electrochemical performance of lithium iron phosphate materials can be more accurately evaluated. These steps can be implemented by using an electrochemical workstation for testing and using professional software to analyze and calculate the test data.
[0136] The above method in the present application adopts the combination of normalized capacity and integration scheme to eliminate the interference of slight changes in the button voltage curve on the test results, and uses the polarization factor to directly feedback the polarization size of the material, which is more accurate. The larger the polarization factor, the greater the polarization of the material and the lower the energy efficiency of the whole battery.
[0137] Furthermore, the preset lithiation depth range is 40% to 100%;
[0138] Furthermore, the preset voltage range is 2.00V to 3.75V.
[0139] Furthermore, the rectangular region where the voltage-lithiation depth curve is located is a rectangular region with 40% to 100% lithiation depth as the horizontal side, and with the value of 40% lithiation depth as the base point and the vertical side with the height of 2.00V to 3.75V.
[0140] Lithium depth refers to the degree to which lithium ions are embedded in or removed from electrode materials during the battery's charge and discharge process. A lithiation depth range of 40% to 100% means that the test focuses on the lithium state in the second half of the battery discharge process, which usually corresponds to the area with higher battery discharge voltage.
[0141] In the experiment, only the data of the battery discharged from 40% lithiation depth to full discharge (100% lithiation depth) were considered, thus obtaining a test result focusing on the performance of the battery in the high voltage region, which helps to evaluate the performance and stability of the battery at high voltage.
[0142] This range can be more helpful in identifying polarization phenomena that may occur in batteries at high voltages, providing important information for battery design and material selection.
[0143] The voltage range defines the voltage interval considered during the battery discharge process. The standard voltage platform of lithium iron phosphate batteries is usually around 3.2V to 3.7V, which is slightly lower than the full discharge voltage of the battery, probably considering the safety and cycle life of the battery.
[0144] During the battery discharge process, data in the voltage range of 2.00V to 3.75V is recorded, and the discharge data outside this range is ignored, thereby obtaining a test result that focuses on the performance near the battery voltage platform, which helps to evaluate the energy efficiency and polarization characteristics of the battery in this voltage range.
[0145] This voltage range helps optimize the battery's operating range, improve the battery's energy efficiency and cycle stability, while avoiding damage caused by over-discharge.
[0146] Furthermore, the target polarization factor is calculated as follows:
[0147]
[0148] Wherein, α represents the target polarization factor; S0 represents the target curve integral area; S1 represents the target rectangular area.
[0149] The integrated area S0 represents the energy released by the battery during the discharge process. By integrating the area under the curve of voltage changing with lithiation depth, the total energy output by the battery during the entire discharge cycle can be obtained. Using mathematical integration methods, such as numerical integration (e.g., Simpson's rule or trapezoidal rule), the area under the curve is calculated to obtain a quantitative measure of the energy change during battery discharge, namely the integrated area.
[0150] The rectangular area S1 represents the theoretical energy output of the battery within a specific lithiation depth and voltage range, which is used to compare with the actual discharge situation. Specifically, by determining the preset range of lithiation depth and voltage, the area of the rectangle is calculated, so that the theoretical energy output area of the battery under the preset conditions can be obtained. Specifically, the product of the length and width of the rectangle can be directly calculated.
[0151] The polarization factor α is the ratio of the actual energy output of the battery to the theoretical energy output, reflecting the energy efficiency and polarization degree of the battery. Substitute the results obtained in steps S1131 and S1132 into the formula to calculate and obtain the target polarization factor.
[0152] Furthermore, the target battery is subjected to a charge-discharge cycle, wherein the number of cycles is not less than 2 times;
[0153] As mentioned above, the number of cycles is not less than 2 to ensure the reliability and repeatability of the test results. Multiple cycles help to accurately evaluate battery performance while reducing the impact of accidental errors.
[0154] Furthermore, the current density range of the charge-discharge cycle is 50 mA / g to 500 mA / g.
[0155] Charging and discharging within this current density range can simulate the performance of the battery under different usage conditions. By testing at different current densities, the performance of the battery at different charge and discharge rates can be evaluated.
[0156] Setting the current density range helps to understand the response of the battery under different charging and discharging conditions, and provides a basis for battery application design.
[0157] Furthermore, before the step S100, respectively testing and calculating the polarization factors of the electrochemical performance of the standard battery including the standard lithium iron phosphate material with known energy efficiency and the battery to be tested including the lithium iron phosphate material to be tested, further includes:
[0158] Step S200, preparing a standard sample and a sample to be tested respectively; wherein the standard sample is a positive electrode sheet prepared from a lithium iron phosphate material with known energy efficiency; and the sample to be tested is a positive electrode sheet prepared from a lithium iron phosphate material to be tested;
[0159] Step S300, assembling the standard sample and the sample to be tested respectively to obtain a standard battery including the standard sample and a battery to be tested including the sample to be tested.
[0160] The above steps involve the preparation of standard samples and test samples and the battery assembly process. To ensure the accuracy and comparability of the test, the performance of the material to be tested can be more accurately evaluated by using standard samples and test samples with known energy efficiency.
[0161] Specifically, the standard sample and the sample to be tested are prepared into positive electrode sheets respectively, and assembled into a standard battery and a battery to be tested, so as to obtain a standard battery and a battery to be tested that can be used for electrochemical performance testing.
[0162] Lithium iron phosphate materials can be made into pole pieces suitable for battery assembly through physical mixing and coating techniques.
[0163] Furthermore, the step S200, respectively preparing the standard sample and the sample to be tested, comprises:
[0164] Step S210, dispersing the conductive material, the lithium iron phosphate material, and the binder into a dispersant to obtain a homogeneous slurry;
[0165] The above steps ensure the uniformity and consistency of the electrode material. The conductive material, lithium iron phosphate material and binder are dispersed in the dispersant to obtain a uniform slurry for easy coating.
[0166] This step can improve the electrochemical properties of the electrode and the overall performance of the battery.
[0167] Specifically, a high-speed stirrer or a ball mill can be used for mixing.
[0168] Step S220, coating the homogenized slurry on the surface of the carbon-coated aluminum foil, and drying to obtain the standard sample and the sample to be tested.
[0169] The above steps involve coating and drying to form a uniform electrode layer.
[0170] The homogenized slurry is coated on the surface of the carbon-coated aluminum foil and dried to obtain a dry electrode sheet ready for battery assembly.
[0171] The drying process helps to remove the solvent and enhance the stability of the electrode structure. A coater can be used for uniform coating and then dried in an oven.
[0172] Further, the conductive material includes at least one of carbon nanotubes, graphene and conductive carbon black;
[0173] Further, the binder includes polyvinylidene fluoride;
[0174] Further, the dispersant used includes N-methylpyrrolidone;
[0175] Furthermore, the surface density of the standard sample and the sample to be tested are both 100 g / m2 to 180 g / m2.
[0176] The present invention is further described below by means of specific examples, but it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0177] Example
[0178] In this embodiment, the energy efficiency of the lithium iron phosphate material is tested using the following method.
[0179] Experimental methods:
[0180] (1) Preparation of pole piece:
[0181] Prepare standard samples (4) and a sample to be tested (1) respectively; wherein the standard sample is a positive electrode sheet prepared from a lithium iron phosphate material with known energy efficiency; and the sample to be tested is a positive electrode sheet prepared from a lithium iron phosphate material to be tested; the specific method is as follows:
[0182] Conductive material, lithium iron phosphate material (including lithium iron phosphate material with known energy efficiency and unknown lithium iron phosphate material) and binder are dispersed in a dispersant to obtain a homogeneous slurry, and the slurry is coated on the surface of carbon-coated aluminum foil, and then dried to obtain a lithium iron phosphate positive electrode sheet.
[0183] The conductive material used is one or a mixture of carbon nanotubes, graphene, and conductive carbon black; the binder used is polyvinylidene fluoride (PVDF);
[0184] The dispersant used was N-methylpyrrolidone (NMP).
[0185] The ratio of the conductive material, the lithium iron phosphate material and the binder is 5:90:5;
[0186] The surface density of the lithium iron phosphate positive electrode plate is 100-180g m -2 It is necessary to ensure that the surface density of the standard sample and the sample to be tested in the same group of experiments is the same, which is 150 g m -2 .
[0187] (2) Assembling the battery: Using the metal lithium sheet as the reference electrode and the lithium iron phosphate positive electrode sheet as the working electrode, assemble a button half-cell.
[0188] (3) Perform electrochemical tests on the assembled button cells:
[0189] At 17mA g -1 The current density was 170 mA g -1 The charge and discharge process was cycled 5 times with a current density of 2.0-3.75V. The voltage range was 2.0-3.75V, and the current density was calculated based on the mass of lithium iron phosphate in the electrode.
[0190] (4) Take 170mAg -1 The discharge voltage curve of the fifth cycle process at the current density of , further select the voltage curve in the range of 40% to 100% of the lithiation depth, calculate its integral of the lithiation depth, and record the integral area as S0;
[0191] Take the voltage corresponding to 40% lithium depth and plot it as follows Figure 2 The area of the rectangle shown is calculated to be S1.
[0192] The formula for the polarization factor is:
[0193] The polarization factors of the battery to be tested and the standard battery are obtained respectively.
[0194] Table 1. Energy efficiency and polarization factor data of samples
[0195] sample Energy efficiency Polarization Factor Standard sample 1 95.2% 102.5% Standard sample 2 94.9% 102.7% Standard sample 3 94.4% 103.2% Standard sample 4 94.1% 103.5% Samples to be tested <![CDATA[E x ]]> 102.9%
[0196] (5) According to the polarization factor corresponding to the standard battery and the energy efficiency of the lithium iron phosphate material, a standard polarization factor-energy efficiency relationship diagram is drawn. As shown in Table 1, based on the energy efficiency data and polarization factor of the standard sample, it can be concluded that Figure 3 The relationship between polarization factor and energy efficiency is shown.
[0197] By fitting the data mathematically, we can get the energy efficiency, and the relationship equation is as follows:
[0198] E=-1.0757α+2.0542;R 2 =0.9947.
[0199] Here, α represents the polarization factor.
[0200] (6) Based on the calculated polarization factor α of the battery under test (using iron-lithium material with unknown energy efficiency) x =102.9%, and put it into the obtained standard polarization factor-energy efficiency relationship diagram to obtain the material energy efficiency Ex =94.7%. x That is the predicted value of energy efficiency of the sample to be tested.
[0201] In summary, the above-mentioned detection method provided by the present invention can achieve the effects of improving test accuracy, shortening test cycle, reducing costs, simplifying operating procedures, enhancing environmental adaptability, improving data repeatability, and promoting material optimization, etc., providing an efficient, economical and reliable solution for the research and development and application of lithium iron phosphate materials.
[0202] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for detecting energy efficiency of lithium iron phosphate material, characterized in that: include: The polarization factors of the electrochemical performance of a standard battery including a standard lithium iron phosphate material with known energy efficiency and a battery to be tested including the lithium iron phosphate material to be tested are obtained by testing and calculating respectively, and the energy efficiency of the lithium iron phosphate material to be tested in the battery to be tested is calculated by comparing the energy efficiency and the polarization factor of the standard battery; Preferably, the standard batteries of the standard lithium iron phosphate material with known energy efficiency are multiple groups, and the energy efficiency of the standard lithium iron phosphate material used in each group is different; Preferably, the number of groups of standard batteries of standard lithium iron phosphate material with known energy efficiency is no less than 3.
2. The method for detecting energy efficiency of lithium iron phosphate material according to claim 1, characterized in that: The standard battery and the battery to be tested are both button-type half-cells.
3. The method for detecting energy efficiency of lithium iron phosphate material according to claim 1, characterized in that: The method of respectively testing and calculating the polarization factor of the electrochemical performance of a standard battery including a standard lithium iron phosphate material with known energy efficiency and a battery to be tested including the lithium iron phosphate material to be tested, and calculating the energy efficiency of the lithium iron phosphate material to be tested in the battery to be tested by comparing the energy efficiency and the polarization factor of the standard battery, comprises: Performing electrochemical tests and calculations on the standard battery and the battery to be tested respectively to obtain a first polarization factor corresponding to the standard battery and a second polarization factor corresponding to the battery to be tested; Constructing a standard polarization factor-energy efficiency relationship diagram according to the first polarization factor of the standard battery and its corresponding energy efficiency; Based on the standard polarization factor-energy efficiency relationship diagram, the energy efficiency corresponding to the battery to be tested is calculated using the second polarization factor.
4. The method for detecting energy efficiency of lithium iron phosphate material according to claim 3, characterized in that: The electrochemical tests and calculations are performed on the standard battery and the battery to be tested respectively to obtain a first polarization factor corresponding to the standard battery and a second polarization factor corresponding to the battery to be tested, including: The standard battery and the battery to be tested are used as target batteries and tested by the following methods respectively: Performing charge and discharge cycles on the target battery, and recording the discharge voltage-specific capacity curve of the last cycle process; Converting the discharge voltage-specific capacity curve into a voltage-lithiation depth curve within a preset lithiation depth range; According to the voltage-lithiation depth curve, a target polarization factor corresponding to the target battery is obtained; the target polarization factor includes the first polarization factor of the standard battery and the second polarization factor of the battery to be tested.
5. The method for detecting energy efficiency of lithium iron phosphate material according to claim 4, characterized in that: The step of obtaining a target polarization factor corresponding to the target battery according to the voltage-lithiation depth curve includes: Calculate the target curve integral area of the target battery according to the voltage-lithiation depth curve; Based on the preset lithiation depth range and the preset voltage range, intercepting a rectangular area including the voltage-lithiation depth curve, and calculating a target rectangular area of the rectangular area; Calculating a target polarization factor of the target battery according to the target curve integral area and the target rectangular area of the target battery; Preferably, the preset lithiation depth ranges from 40% to 100%; Preferably, the preset voltage range is 2.00V to 3.75V.
6. The method for detecting energy efficiency of lithium iron phosphate material according to claim 5, characterized in that: The rectangular region where the voltage-lithiation depth curve is located is a rectangular region with 40% to 100% lithiation depth as the horizontal side, and 40% lithiation depth as the base point and a height of 2.00V to 3.75V as the vertical side.
7. The method for detecting energy efficiency of lithium iron phosphate material according to claim 5, characterized in that: The target polarization factor is calculated as follows: Wherein, α represents the target polarization factor; S0 represents the target curve integral area; S1 represents the target rectangular area.
8. The method for detecting energy efficiency of lithium iron phosphate material according to claim 4, characterized in that: The target battery is subjected to a charge-discharge cycle, wherein the number of cycles is not less than 2 times; Preferably, the current density of the charge-discharge cycle ranges from 50 mA / g to 100 mA / g.
9. The method for detecting energy efficiency of lithium iron phosphate material according to claim 1, characterized in that: Before respectively testing and calculating the polarization factors of the electrochemical performance of the standard battery including the standard lithium iron phosphate material with known energy efficiency and the battery to be tested including the lithium iron phosphate material to be tested, the method further includes: A standard sample and a sample to be tested are prepared respectively; wherein the standard sample is a positive electrode sheet prepared from a lithium iron phosphate material with known energy efficiency; and the sample to be tested is a positive electrode sheet prepared from a lithium iron phosphate material to be tested; The standard sample and the sample to be tested are assembled separately to obtain a standard battery including the standard sample and a battery to be tested including the sample to be tested.
10. The method for detecting energy efficiency of lithium iron phosphate material according to claim 9, characterized in that: The step of separately preparing the standard sample and the sample to be tested comprises: Dispersing the conductive material, the lithium iron phosphate material, and the binder into a dispersant to obtain a homogeneous slurry; The homogenized slurry is coated on the surface of the carbon-coated aluminum foil, and the standard sample and the sample to be tested are obtained after drying; Preferably, the conductive material comprises at least one of carbon nanotubes, graphene and conductive carbon black; Preferably, the binder comprises polyvinylidene fluoride; Preferably, the dispersant used comprises N-methylpyrrolidone; Preferably, the surface density of the standard sample and the sample to be tested are both 100 g / m2 to 180 g / m2.